Bram Stoker a biography of the author of Dracula - Belford, Barbara 1935-2010 (A Borzoi book, 1996)
We follow Stoker from his sickly childhood - entertained by his mother's twice-told tales of Irish hobgoblins and banshees - to his years as a Dublin undergraduate student and newspaperman, when he first wrote to his idol Walt Whitman, spilling out his innermost thoughts and beginning a lifelong correspondence that culminated in their meeting when Stoker traveled to America on tour with Irving and Ellen Terry. We see Stoker's childhood friendship with Oscar Wilde, and watch as the two young men compete for the hand of the beautiful Florence Balcombe, who became Stoker's wife. And we see Stoker in the literary and theatrical circles of Victorian London among such figures as Mark Twain, Arthur Conan Doyle, James Whistler, Lord Tennyson, and George Bernard Shaw